Wat maak ons met die skarminkel in die jonkmanskas, of: aspekte van die gesag van die woordeboek - Odendal, F.F. (Lexikos, 1991)
Aspects of the Authority of the Dictionary It is a well-known fact that the man in the street looks upon the dictionary as a final and undisputed authority. This means the lexicographer carries an immense responsibility. In particular, his linguistic facts must be above suspicion. How difficult it is always to ascertain these facts, is illustrated with respect to a number of cases. Special attention is also focused on the problem of shift in meaning still in drift. Subsequently, the question of the opposition descriptive/prescriptive is discussed. Most linguists pay lip-service to the point of view that a dictionary may only be descriptive. The author tries to demonstrate that no dictionary complies with this requirement: the omission of a word or a form is in itself a prescription; furthermore the language of the educated, of a certain respected class is described, not that of all speakers. The user of the dictionary demands guidance, and clear guidance at that. The author takes the position at present, in contrast to his previous stance, that the lexicographer, in particular the writer of a desk dictionary, must not hesitate to give this clear guidance, i.e. be prescriptive, even in a blatant manner if need be.